Developing Various Herbal MSME Products by Processing Herbal Tea Made from Lotus Flowers (Nelumbo Nucifera): Pengembangan Produk UMKM Aneka Herbal dengan Pengolahan Teh Herbal Berbahan Bunga Lotus (Nelumbo Nucifera) - Rita Khairina; Dewi Kartika Sari; Yuspihana Fitrial (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
Tea drinks made from the roots, bark, leaves, and flowers of plants other than tea are known as herbal teas. Tea made from lotus leaves and flowers is known as lotus tea. The purpose of this activity is to provide knowledge and skills to the Aneka Herbal MSME about the benefits and processing of herbal tea made from lotus flowers and leaves. Observations identified that lotus plants are found throughout the year in swampy areas and rice fields around the Gambut and Kertak Hanyar Districts of Banjar Regency, where the Aneka Herbal MSME is domiciled. The local community is not yet aware that lotus plants have the advantage of being a functional beverage in the form of herbal tea, so they have not utilized the plant as a source of family income. This activity was carried out in the form of counseling, attended by 20 housewives who live around the Aneka Herbal MSME. The counseling material was about the functional benefits of brewing lotus flower herbal tea. After the training activity, the Aneka Herbal MSME was interested in expanding their product range by making herbal tea in small packages under the Nutrilotus brand. The product will be marketed together with other existing herbal products every Sunday morning in the Sunday Market area of ​​Kertak Hanyar District, Banjar Regency.